การวางนัยทั่วไปของปัญหาวันเกิด - เพ็ญพิชชา เศรษฐพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
In 1939, Richard von Mises raised the interested question "how many people must be gathered before the probability of two people sharing a birthday exceeds 50 %" which leads to a general question "the probability that at least two people in a group of n people will have the same birthday". The question is called the "Birthday Problem". Then, many mathematicians generalized the problem to the case of at least m out of n people having the same birthday where 2 ≤ m ≤ 5. In this project, we will investigate the probability of at least m out of n people sharing a birthday where 2 ≤ m ≤ n, and will approximate the probability by Poisson distribution.